On Testing Business Models - Huelsbeck, David P; Merchant, Kenneth A; Sandino, Tatiana (The Accounting Review, 2011)
ABSTRACT This study explores decisions related to formal empirical tests of business models and interpretations and uses of those tests. Business models describe managers' rationales as to how their organizations will achieve success. This study documents a test of one company's business model under seemingly favorable conditions for such a test—a successful single-product firm following a consistent strategy over a long period of time with stable management and publicly traded stock. Although the findings provide only weak support for the hypothesized business model, the confidence of the company's top managers in their business model remained high. Further analyses reveal that the managers' response to the test results is consistent with that expected of Bayesian-rational agents. Our analyses provide the basis for development of a framework for understanding the expected value of testing business models in various circumstances. This framework might explain apparent contradictions between previous studies containing normative statements regarding the value of testing business models. Data Availability: The data used in this study are derived from a proprietary dataset and public sources.